Надійність високовольтних вузлів систем електроживлення бортових технологічних пристроїв - Юрченко, М.М.; Юрченко, О.М.; Твердохліб, Ю.О.; Сенько, В.І. (Технічна електродинаміка, 2012)
It is being considered particularities of high voltage power supply systems for on-board technological set-ups with taking into account modern requirements to their reliability and life.